Exploring the trophic niche characteristics of four carnivorous Cultrinae fish species in Lihu Lake, Taihu Basin, China - Wang, Yuan; Ren, Long; Xu, Dong-po; Fang, Di-an (Frontiers in Ecology and Evolution, 2022)
This study found significant differences between the standard length distributions of humpback and redfin culter and between Mongolian culter and topmouth culter. A stable isotope analysis (δ13C and δ15N) was used to investigate the inter-species differences between the feeding habits and trophic niches of four carnivorous species of Cultrinae fish. The results showed that the δ13C and δ15N values were significantly correlated with the standard length and species. However, the δ13C values of humpback and redfin culter were not significantly different, suggesting that these two fish species had similar food sources. The δ15N values of Mongolian culter and topmouth culter were the highest, suggesting that they occupied a higher trophic level and that animal prey are more important in their diets. Moreover, variations in δ13C and δ15N indicated considerable niche overlap and interspecific competition among the four species. We also evaluated trophic niches, diversity, redundancy, and evenness utilizing isotopic niche metrics, and we estimated asymmetrical niche overlaps. The analysis revealed that four carnivorous species of Cultrinae displayed similar trophic niche sizes and trophic diversity. The trophic traits of topmouth culter clearly defined them as trophic generalist in terms of the inter-individual variability in their isotopic niches. A significant finding was that the average niche overlap between them was as high as 64.02%; topmouth culter had the greatest trophic overlap with redfin culter (95.52%) and humpback (90.38%), followed by Mongolian culter onto redfin culter (85.32%), indicating that topmouth culter and Mongolian culter benefit the most from the food supply in the habitat, or they are more competitive in the presence of limited resources.